2006
DOI: 10.1002/cbic.200600119
|View full text |Cite
|
Sign up to set email alerts
|

Oligo(ethylene glycol) Derivatives of Thioflavin T as Inhibitors of Protein–Amyloid Interactions

Abstract: Molecular coatings on biological surfaces. Small molecules that bind to and coat Alzheimer's related β‐amyloid fibrils can function as inhibitors of the interaction of amyloid‐binding proteins with these fibrils. Derivatives of thioflavin T are shown to inhibit the binding of a monoclonal anti‐Aβ IgG, human catalase, and recombinant human ABAD to in vitro‐grown amyloid fibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…These observations are consistent with the hypothesis that H 2 O 2 , or its metabolites, but not superoxide, play a dominant role in 〈␤-induced oxidative stress. Moreover, Milton et al (21) and our previous work (55) revealed that 〈␤ binds directly to catalase in cell free assays, whereas 〈␤ does not bind to GPx (supplemental Fig. S12).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…These observations are consistent with the hypothesis that H 2 O 2 , or its metabolites, but not superoxide, play a dominant role in 〈␤-induced oxidative stress. Moreover, Milton et al (21) and our previous work (55) revealed that 〈␤ binds directly to catalase in cell free assays, whereas 〈␤ does not bind to GPx (supplemental Fig. S12).…”
mentioning
confidence: 76%
“…These results are consistent with the possibility that the BTA-EG x molecules were capable of entering cells and could, hence, interact with intracellular pools of A␤ peptides. We hypothesize that this interaction between the BTA-EG x molecules and A␤ protected cells from harmful protein-amyloid interactions by forming protein-resistant molecular surface coatings on A␤ (55). Such a mechanism would explain the observed reduction in intracellular co-localization of catalase and A␤ in the presence of the BTA-EG x molecules.…”
Section: Bta-eg X Molecules Readily Internalize In Cells and Reduce Tmentioning
confidence: 90%
See 3 more Smart Citations